Unity for Whom? Theological Reflections on South Africa’s 2024 Government of National Unity - Vilakati, Vusi (Stellenbosch theological journal, 2024)
Three decades into South Africa’s democracy, the 2024 elections precipitated a significant political shift, solidifying coalition governance and prompting the re-emergence of a Government of National Unity (GNU). This article analyses the GNU’s potential and challenges within this evolving political landscape, specifically examining the intersection of theology and governance. Drawing upon economic and social justice, unity, social cohesion, partnership, and ethical governance themes, the article explores how theological insights can shape political discourse and leadership. It posits that the church holds a crucial prophetic role in advocating for transformation, stewardship, and ethical governance, ultimately striving for a more just, equitable, and unified society. By integrating theological perspectives into the analysis of coalition politics and governance, this article provides a nuanced understanding of its implications for South African society.